KINERJA PEGAWAI DITINJAU DARI BUDAYA ORGANISASI, LINGKUNGAN KERJA DAN TAMBAHAN PENGHASILAN PEGAWAI PADA BAGIAN UMUM SETDA KABUPATEN BANJARNEGARA - Hayati, Sri; Lustono, Lustono; Haryani, Titik (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2023)
ABSTRACT Employee performance has a very important role because performance is the final result of the process of employees completing their tasks. Employees will be able to carry out their duties properly if they are supported by a good organizational culture, a suitable work environment and sufficient additional income so that optimal results can be achieved. An overview of the activities that occur at this time in the General Section of the Banjarnegara Regency Secretariat still found employees who do not comply with agency regulations, this will lead to inefficiency in a person's work and can further reduce performance. The purpose of this study was to analyze the influence of organizational culture, work environment and additional employee income in the General Section of the Regional Secretariat of Banjarnegara Regency either partially or simultaneously. The research method used is a quantitative method with a population of 87 respondents, by taking samples from all populations. The data collection technique used is distributing questionnaires. The data analysis method used is multiple linear regression with validity test, reliability test, normality test, heteroscedasticity test and multicollinearity test. To test the hypothesis using the t test and F test. The results of this study indicate that the organizational culture variable has a positive and significant effect on employee performance, while the work environment and additional employee income have no effect on employee performance. From the results of the analysis of the coefficient of determination (R²) there is an influence of organizational culture, work environment, and additional employee income of 0.596 (59.6%), meaning that the percentage of organizational culture variables, work environment and additional employee income affects employee performance by 59.6 %. while the remaining 40.4% are variables not examined in this study.